Clinical Profile of High-Altitude Cerebral Edema: A Case Series - Manish Bhartiya; Jatinder Kumar; Rahil Arora; Ankush Dhiman (Annals of Indian Academy of Neurology)
High-altitude cerebral edema (HACE) is a severe form of altitude sickness characterized by headache, ataxia, and altered consciousness. This study aims to describe the clinical features, radiological findings, and outcomes of patients diagnosed with HACE. This study was conducted at a tertiary care hospital in northeastern India. Eleven consecutive patients diagnosed with HACE based on clinical criteria were included. Clinical data, demographics, radiological findings, and outcome were collected. All 11 patients were young males. Headache was the most common symptom, followed by ataxia. Uncommon findings included retinal hemorrhages in two patients. Cytotoxic lesions of the corpus callosum were present in two patients, while one had micro-hemorrhages in the splenium. All the patients had a good outcome. HACE is a rare but serious condition that requires early recognition and treatment. Diagnosis is primarily clinical, and radiological findings may be normal in some cases.